1999
DOI: 10.1073/pnas.96.4.1415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of biological synergy between cellular Src and epidermal growth factor receptor

Abstract: Overexpression of both cellular Src (c-Src) and the epidermal growth factor receptor (EGFR) occurs in many of the same human tumors, suggesting that they may functionally interact and contribute to the progression of cancer. Indeed, in murine fibroblasts, overexpression of c-Src has been shown to potentiate the mitogenic and tumorigenic capacity of the overexpressed EGFR. Potentiation correlated with the ability of c-Src to physically associate with the activated EGFR and the appearance of two unique in vivo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
367
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(390 citation statements)
references
References 35 publications
(43 reference statements)
16
367
2
2
Order By: Relevance
“…As shown in Figure 3a, the relative degree of phosphorylation at tyrosines 845, 992, 1045 and 1068 was indistinguishable in WT and mutated EGFR, with-and without EGF. We saw no evidence for the selective phosphorylation of tyrosine 845 (primarily a Src phosphorylation site Tice et al, 1999)) reported for the L834R EGFR in mouse mammary epithelial cells , or for enhanced autophosphorylation of Y992 or Y1068 reported for L834R and DL723-P729insS in the same study . Similarly, we could not reproduce the increased Y1045 phosphorylation reported by Chen et al (2006) for EGFR mutants expressed in the H1299 NSCLC cell line.…”
Section: Gefitinib-sensitizing Mutations Enhance Basal Egfr Autophospcontrasting
confidence: 50%
“…As shown in Figure 3a, the relative degree of phosphorylation at tyrosines 845, 992, 1045 and 1068 was indistinguishable in WT and mutated EGFR, with-and without EGF. We saw no evidence for the selective phosphorylation of tyrosine 845 (primarily a Src phosphorylation site Tice et al, 1999)) reported for the L834R EGFR in mouse mammary epithelial cells , or for enhanced autophosphorylation of Y992 or Y1068 reported for L834R and DL723-P729insS in the same study . Similarly, we could not reproduce the increased Y1045 phosphorylation reported by Chen et al (2006) for EGFR mutants expressed in the H1299 NSCLC cell line.…”
Section: Gefitinib-sensitizing Mutations Enhance Basal Egfr Autophospcontrasting
confidence: 50%
“…Distinct from other receptor kinases, phosphorylation of the kinase activation segment of EGFR is not required for activation (Gotoh et al, 1992;Tice et al, 1999). Instead, ligand-activated kinase domains form an asymmetric dimer: ligand (EGF, TGF, HB-EGF) independently binds with low affinity to extracellular domains I and III (LR1, LR2) of ErbB1, inducing a conformational change that facilitates high affinity binding to both domains ( Figure 1).…”
Section: The Egfr Familymentioning
confidence: 99%
“…In addition to cell proliferation, Src also regulates other cellular functions, including cell adhesion, motility and invasion, which change the cell behavior, ultimately contributing to the tumor progression and metastasis (Yeatman, 2004). It has been suggested that direct phosphorylation of the Tyr845 residue of EGFR by Src is a necessary component of Src's role in tumorigenesis (Tice et al, 1999;Ishizawar and Parsons, 2004). Thus, a downstream signaling pathway activated by Src seems to have an essential role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%